CXXC5 plays a role as a transcription activator for myelin genes on oligodendrocyte differentiation. Issue 3 (14th October 2015) - Kim, Mi‐Yeon; Kim, Hyun‐Yi; Hong, Jiso; Kim, Daesoo; Lee, Hyojung; Cheong, Eunji; Lee, Yangsin; Roth, Jürgen; Kim, Dong Goo; Min, Do Sik; Choi, Kang‐Yell
Abstract : Myelination in corpus callosum plays important role for normal brain functions by transferring neurological information between various brain regions. However, the factors controlling expression of myelin genes in myelination are poorly understood. Here, CXXC5, a recently identified protein with CXXC‐type zinc finger DNA binding motif, was characterized as a transcriptional activator of major myelin genes. We identified expression of CXXC5 expression was increased by Wnt/β‐catenin signaling. CXXC5 specifically expressed in the white matter induced expression of myelin genes through the direct binding of CXXC DNA‐binding motif of CXXC5 on the MBP promoter. During the differentiation of neural stem cells (NSCs) of CXXC5 −/− mice, the expressions of myelin genes were simultaneously reduced. The CXXC5 −/− mice exhibited severely reduction of myelin genes expression in corpus callosum as well as abnormalities in myelin structure. The disrupted structural integrity of myelin in the CXXC5 −/− mice resulted in reduced electrical conduction amplitudes at corpus callosum. These findings indicate that the regulation of myelin genes expression by CXXC5 is important for forming myelin structure involved with axonal electrical signal transfer in the corpus callosum. GLIA 2016;64:350–362 Main Points: CXXC5 is a transcriptional activator of myelin genes in the corpus callosum. Timing of myelin gene expression by CXXC5 is important for myelin structure. Abnormal myelination by CXXC5 deficit impaired interhemispheric transfer.